2023
DOI: 10.3390/ani13132199
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Potential of Orange Pulp for Improving Laying Rate, Egg Quality, Oxidative Stability, Fatty Acids Composition, and Reproductive Tract Morphology of Laying Hens

Abstract: The current study aimed to demonstrate the effects of dietary dried orange pulp (DOP) on the laying performance, egg quality, antioxidant status, yolk fatty acid composition, serum biochemistry, and reproductive tract morphology of laying hens. A total of 200 Lohman Brown Lite laying hens were randomly allotted into 4 dietary treatments with 10 replicates each. The experimental treatment groups were the control group, a basal diet containing 50 g DOP/kg feed (DOP5%), a basal diet containing 70 g DOP/kg feed (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
(97 reference statements)
0
1
0
Order By: Relevance
“…The yolk develops in the ovary and moves through the infundibulum into the oviduct, and its quality relies on its size, color, and nutritional content [ 10 ]. Numerous plant extracts have been found to improve egg quality by enhancing the oviduct health of laying hens [ 11 , 12 , 13 , 14 ]. Research on thyme [ 15 ] and rosemary [ 16 ] extracts have demonstrated their antimicrobial and antioxidant properties, indicating a positive impact on egg quality.…”
Section: Introductionmentioning
confidence: 99%
“…The yolk develops in the ovary and moves through the infundibulum into the oviduct, and its quality relies on its size, color, and nutritional content [ 10 ]. Numerous plant extracts have been found to improve egg quality by enhancing the oviduct health of laying hens [ 11 , 12 , 13 , 14 ]. Research on thyme [ 15 ] and rosemary [ 16 ] extracts have demonstrated their antimicrobial and antioxidant properties, indicating a positive impact on egg quality.…”
Section: Introductionmentioning
confidence: 99%
“…In poultry production, nutrition occupies a prominent place since feeding is one of the costliest factors in breeding. According to [1,2], among the nutrients necessary for bird development, lipids stand out as sources of fatty acids that act in various metabolic functions of the organism. Nutrient adequacy, such as fatty acids for birds, can occur traditionally through the diet provided and be formulated according to recommendations for each animal phase by adding lipid sources rich in fatty acids derived from vegetable oils or animal fat [3].…”
Section: Introductionmentioning
confidence: 99%
“…1 -Mineral supplement (Amount per kg of feed): Manganese 82 mg; Iron-58.4 mg; Selenium-0.35 mg; Copper-11.6 mg; Iodine-1.18 mg 2 . Vitamin supplement (Amount per kg of feed): vitamin A-13.493 IU; vitamin D3-3.374 IU; Vitamin E-50.5 IU; Vitamin B1-3.64 IU; vitamin B2-9.0 IU; vitamin B6-5.05 IU; Ac.…”
mentioning
confidence: 99%